2015
DOI: 10.1186/s13071-015-1199-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced aggression and foraging efficiency of invasive signal crayfish (Pacifastacus leniusculus) infested with non-native branchiobdellidans (Annelida: Clitellata)

Abstract: BackgroundBiological invasions are a principal threat to global biodiversity and identifying the determinants of non-native species’ success is a conservation priority. Through their ability to regulate host populations, parasites are increasingly considered as important in determining the outcome of species’ invasions. Here, we present novel evidence that the common crayfish ecto-symbiont, Xironogiton victoriensis (Annelida: Clitellata) can affect the behaviour of a widespread and ecologically important invad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Considering its ability to reproduce in vitro, C. aff. okadai, is likely a facultative symbiont, whereas X. victoriensis, considering its dependency on the host to reproduce and the detrimental effect it is known to have on host behaviour (James et al, 2015b), is an obligate symbiont that may be parasitic. Therefore, whilst both species have established in the UK and are predicted to spread with the dispersal of signal crayfish, X. victoriensis may have greater potential to influence ecosystem structure and function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering its ability to reproduce in vitro, C. aff. okadai, is likely a facultative symbiont, whereas X. victoriensis, considering its dependency on the host to reproduce and the detrimental effect it is known to have on host behaviour (James et al, 2015b), is an obligate symbiont that may be parasitic. Therefore, whilst both species have established in the UK and are predicted to spread with the dispersal of signal crayfish, X. victoriensis may have greater potential to influence ecosystem structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…If niche overlap between these branchiobdellidans was forced, for example by removal of signal crayfish from the River Gavenny for control (reducing the number of available hosts), intraguild predation would likely become more important. Ultimately, this could impact the survival of competitively subordinate X. victoriensis, which are known to reduce the aggression and foraging success of infected crayfish (James et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include local crabs rather than shrimps with more developed grooming behaviour (Du Preez & Smit 2013;Tavakol et al 2016;Douthwaite et al 2018). Recent research suggested altered behaviour of competing branchiobdellids (James et al 2017) and their translocated host (James et al 2015). These previously overlooked consequences (Vedia et al 2015) can be thus expected also among translocated temnocephalids and their hosts.…”
Section: Potential Disease Transmissionmentioning
confidence: 99%
“…This location may facilitate transmission as crayfish often lock chelae during aggressive interactions, but it could also promote desiccation during terrestrial host movements. Although branchiobdellidans are generally considered commensals, X. victoriensis reduces crayfish aggression and foraging efficiency, which could alter signal crayfish invasion success (James et al, 2015c). Here, we tested whether these aquatic ectosymbionts can tolerate amphibious host behaviour, which in turn could affect symbiont dispersal with potential consequences for host invasion dynamics.…”
Section: Introductionmentioning
confidence: 99%